Meningkatkan Kemampuan Menulis Siswa dengan Modul Elektronik Terintegrasi Model FIVES dalam Pembelajaran Campuran di SD Negeri 01 Abepura Kota Jayapura - Yan Dirk Wabiser; Sario Itlay (Jurnal Pengabdian Masyarakat Waradin, 2023)
The background of this study focuses on the challenges faced by students in writing skills at SD Negeri 01 Abepura, which showed less than satisfactory results in writing tests. The purpose of this study was to improve students' writing skills by implementing an integrated electronic module of the FIVES model in blended learning. The methodology used was classroom action research (CAR) with two cycles, involving 30 students as research subjects. The results showed that the implementation of the FIVES model could significantly improve students' writing skills, with the average writing score increasing from 65 in the first cycle to 80 in the second cycle. The discussion indicated that the use of interactive electronic modules and varied learning strategies could increase student motivation and engagement. The conclusion of this study confirms that the FIVES model is effective in improving students' writing skills, and it is recommended to be implemented in learning in other elementary schools.